Efektivitas Pembiayaan Kredit Usaha Rakyat Mikro Syariah pada Bank Syariah Indonesia Terhadap Pengembangan UMKM di Kota Takengon - Putra, Ihdina; Hasnita, Nevi; Ridla, Ismail Rasyid (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
Sharia Micro People's Business Credit (KUR) is an interest-free financing program distributed under Islamic principles with the aim of increasing access to capital, competitiveness, and the growth of micro enterprises. This study aims to determine the effectiveness of Sharia Micro KUR financing at Bank Syariah Indonesia (BSI) in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Takengon City. The research method used is descriptive qualitative with a field study approach through interviews, observations, and documentation. The results show that Sharia Micro KUR financing at BSI is quite effective, in terms of target accuracy, timing, financing amount, credit burden, and procedural ease. This financing has significant impacts on increasing income, customer numbers, product quality, and employment absorption. Thus, Sharia KUR in Takengon City plays an important role in strengthening the MSME sector.